2018
DOI: 10.1002/1873-3468.13227
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan‐4 influences mammalian myoblast proliferation by modulating myostatin signalling and G1/S transition

Abstract: Myostatin, a TGF‐β superfamily member, is a negative regulator of muscle growth. Here we describe how myostatin activity is regulated by syndecan‐4, a ubiquitous transmembrane heparan sulfate proteoglycan. During muscle regeneration the levels of both syndecan‐4 and promyostatin decline gradually after a sharp increase, concurrently with the release of mature myostatin. Promyostatin and syndecan‐4 co‐immunoprecipitate, and the interaction is heparinase‐sensitive. ShRNA‐mediated silencing of syndecan‐4 reduces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 56 publications
3
27
0
Order By: Relevance
“…Other studies observed reduced motility following syndecan-4 knockdown in different cell types, consistent with our current observations, whereas high syndecan-4 level promoted migration (Toba-Ichihashi et al, 2016;Yin et al, 2017;Jeyarajah et al, 2019). Previous analyses of C2C12 mouse myoblast cells revealed that syndecan-4 was the most prominent heparan sulfate proteoglycan in these cells when compared with syndecan-1, syndecan-2, syndecan-3, glypican, or perlecan (Keller-Pinter et al, 2018), thus suggesting an important role for syndecan-4 in this cell type. However, the observed upregulation of syndecan-1, syndecan-2, and syndecan-3 mRNAs after syndecan-4 silencing (Keller-Pinter et al, 2018) suggests that other members of the syndecan family may compensate at least partially for the loss of syndecan-4.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Other studies observed reduced motility following syndecan-4 knockdown in different cell types, consistent with our current observations, whereas high syndecan-4 level promoted migration (Toba-Ichihashi et al, 2016;Yin et al, 2017;Jeyarajah et al, 2019). Previous analyses of C2C12 mouse myoblast cells revealed that syndecan-4 was the most prominent heparan sulfate proteoglycan in these cells when compared with syndecan-1, syndecan-2, syndecan-3, glypican, or perlecan (Keller-Pinter et al, 2018), thus suggesting an important role for syndecan-4 in this cell type. However, the observed upregulation of syndecan-1, syndecan-2, and syndecan-3 mRNAs after syndecan-4 silencing (Keller-Pinter et al, 2018) suggests that other members of the syndecan family may compensate at least partially for the loss of syndecan-4.…”
Section: Discussionsupporting
confidence: 91%
“…Although syndecan-4 knockout mice cannot regenerate damaged muscle tissue (Cornelison et al, 2004), the details of the underlying mechanism remain unknown. Previously, we reported that syndecan-4 affects myoblast proliferation by modulating myostatin signaling and the G1/S transition in cell cycle (Keller-Pinter et al, 2018), and directional persistence of random cell migration is affected by syndecan-4-mediated Tiam-1 expression and distribution (Becsky et al, 2020). In this study, we demonstrated that syndecan-4 knockdown induced nanoscale alterations in the lamellipodial actin fiber structure of migrating myoblasts.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…It is noteworthy that the direct relationship between the syndecan-4 coordinated persistent migration and the Tiam1-mediated Rac1 activation remains unknown. Earlier, we reported that syndecan-4 binds and inhibits Tiam1, modulating the activity of Rac1 GTPase [24]. Thus, the syndecan-4-Tiam1 complex can regulate the local activity of Rac1.…”
Section: Discussionmentioning
confidence: 85%
“…We verified the effect of syndecan-4 (SDC4) silencing by qPCR technique and Western blotting in C2C12 mouse myoblast cell lines transfected stably with plasmids expressing shRNA specific for syndecan-4 (shSDC4#1 and shSDC4#2), and we also tested the effect of the scrambled sequence [24]. The syndecan-4 expression was significantly decreased in both shSDC4#1 and shSDC4#2 cell lines, with the reduction being less in the latter; whereas the scrambled sequence did not affect the syndecan-4 level [24].…”
Section: Syndecan-4 Silencing Reduces Myoblast Migration In a Random mentioning
confidence: 90%